THE EFFECT OF LEARNING INDEPENDENCE ON CLASS XI ACCOUNTING STUDENTS’ LEARNING OUTCOMES IN THE TRADING COMPANY ACCOUNTING SUBJECT AT SMK BINA PROFESI PEKANBARU - Fajar Prasetyo; Suarman Suarman; Mujiono Mujiono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the effect of independent learning on class XI accounting students’ learning outcomes in the learning subject of trading company accounting at SMK Bina Profesi Pekanbaru. The research uses a type of quantitative descriptive research. The sample was 32 accounting students from class XI in the academic year 2022/2023. Data were collected through questionnaires and documentation, which were subsequently analyzed through simple linear regression data analysis techniques and the coefficient of determination. The results indicate that independent learning had a positive and significant effect on learning outcomes with an effect of 40.9% and the rest was influenced by other factors, which were not discussed in the research like students’ motivation. Thus, it can be concluded that students’ learning outcomes will increase if there is independent learning carried out by the students themselves. Hence, it is expected for teachers to improve student’s learning outcomes by concerning more on increasing the independence of the students themselves.